SISTEM INFORMASI GEOGRAFIS LOKASI SMA DI KOTA PADANG BERBASIS WEB - Riska Amelia (Universitas Negeri Padang, 2016)
This research aims to provide information and facilitate the community in obtaining information about the location of the HIGH SCHOOL that's located in the city of Padang. The design of this system using the Google Maps API and combine files map KML (Keyhole Markup Language) to display a map of a location that has a limit on each sub district of the city of Padang. Design and analysis method used in this research using model waterfall which stages the starting of system engineering, requirements analysis, system design using modeling languages Unified Modeling Language (UML), the implementation of the program code using a web based programming language i.e. the Hypertext Markup Language (HTML), Pre-Hypertext Processor (PHP), Cascading Style sheets (CSS), JQuery and MySQL as the database. The results of research is an application web-based geographic information System in the city of Padang.